56.0k views
24 votes
Can someone help me with this? its solving systems by substitution

Can someone help me with this? its solving systems by substitution-example-1
User Nebkat
by
5.2k points

1 Answer

11 votes
Answer: x = 1 and y = 2

Given:
y = -3x + 5
5x - 4y = -3

Since we are given y, let’s sub it in the second equation.

5x - 4(-3x + 5) = -3
5x + 12x - 20 = -3
17x = 17
x = 1

After finding x, we can now find y.

5(1) - 4y = -3
-4y = -8
y = 2

Checking:

y = -3x + 5
2 = -3(1) + 5
2 = 2


5x - 4y = -3
5(1) - 4(2) = -3
-3 = -3
User Kevin Tong
by
5.5k points